Vector-borne pathogens in cats and associated fleas in southern Ethiopia - Marika Grillini; Hana Tadesse; Alessandra Mondin; Maria Luisa Menandro; Giovanni Franzo; Giorgia Dotto; Antonio Frangipane di Regalbono; Bersissa Kumsa; Rudi Cassini; Giulia Simonato (Parasites & Vectors)
Abstract Background The worldwide increment of cat populations has increased the risk of ectoparasite infestation and feline vector-borne pathogen (VBP) transmission. In low-income countries, such as Ethiopia, favorable climatic conditions and the absence of preventive measures against ectoparasites contribute to broadening VBP circulation. This study aimed to investigate the prevalence of protozoal (i.e., Hepatozoon, Babesia, and Cytauxzoon species) and bacterial (i.e., Anaplasma, Ehrlichia, Rickettsia, and Bartonella species) infections in owned cats and in their ectoparasites in southern Ethiopia. Methods The study was conducted in four districts of the Gamo zone, southern Ethiopia. Cats were sampled, and information about the animals was recorded. Blood samples were collected on Flinders Technology Associates (FTA) cards, while ectoparasites were collected by combing and stored in 70% ethanol. Fleas were morphologically identified, and DNA was extracted from both blood samples and ectoparasites, then submitted to molecular analysis. Real-time polymerase chain reaction (PCR) and end-point PCR were used to detect pathogens. Positive samples were sequenced, and a phylogenetic analysis was performed on the obtained Hepatozoon spp. and Rickettsia spp. sequences. Results Overall, 109 cats were sampled, and 115 fleas (i.e., 28 Ctenocephalides felis and 87 Echidnophaga gallinacea) and three ticks (Haemaphysalis laechi) were collected. Molecular analysis of feline blood samples revealed Hepatozoon spp. as the most common pathogen (36.7%; CI:28.3–46.1%), followed by Rickettsia spp. (5.5%; CI: 2.5–11.5%), Bartonella spp. (2.8%; CI:0.9–7.8%), and Babesia spp. (0.9%; CI:0.2–5.0%); whereas fleas harbored mostly Rickettsia spp. (52.2%; CI:43.1–61.1%), followed by Bartonella spp. (6.1%; CI: 3.0–12.0%), and Hepatozoon spp. (0.9%; CI: 0.2–4.8%). According to phylogenetic clustering, specimens of the Hepatozoon genus were classified as H. felis, H. luiperdjie,, and H. canis. Concerning the genus Rickettsia, it was not possible to reach a clear identification for the majority of the sequences, apart from some specimens ascribable to R. felis and R. asembonensis. Conclusions Vector-borne pathogens posing significant threats to animal and human health were detected in this study. Molecular analysis suggested the circulation of different and genetically variable species in the feline host. The molecular approach allowed the identification of VBPs in the cat population and their fleas, providing new data on their occurrence and prevalence in Ethiopia and, more generally, in sub-Saharan Africa. Graphical abstract